Cotton Cost-Return Budget in South Central and Southeast Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2012)
This publication projects a budget that reflects expected income and costs based on production of cotton in south central and southeast Kansas.
MF939_2012_12
Keywords: MF939; Economics; Crops; MF